Performance Evaluation of a Terminal Gas Turbine Generator of a Simulated and Modeled Gas Plant - K. E. Madu; U. Nosegbe; L. Chukwuka (Journal of Applied Sciences and Environmental Management)
Gas turbine power plants have gained a wide spread acceptance in the power generation and mechanical drive. Their compactness, high power to weight ratio, ease of installation, early commissioning, fast starting and quick shut down time have made them popular prime mover. Hence, the objective of this paper was to investigate the performance evaluation of a terminal gas turbine generator of a gas plant simulated and modeled by MATLAB 2014 to analyze and evaluate the overall efficiency, thermal efficiency, thermal power, heat rate, specific fuel consumption, and work ratio. The results obtained shown that the overall efficiency, average thermal efficiency, average heat rate, average thermal power, average specific consumption, and average work ratio of gas turbine generator were gotten as 22.23%, 23.09%, 16250kW, 5892kW, 0.3390kg/kW-h, and 0.4564. Furthermore, the results revealed that overall efficiency, thermal efficiency, thermal power decrease as a result of increase in compressor inlet temperature.